2018
DOI: 10.1002/brb3.1070
|View full text |Cite
|
Sign up to set email alerts
|

Functional and anatomical connectivity‐based parcellation of human cingulate cortex

Abstract: IntroductionHuman cingulate cortex (CC) has been implicated in many functions, which is highly suggestive of the existence of functional subregions.MethodsIn this study, we used resting‐state functional magnetic resonance imaging (rs‐fMRI) and diffusion tensor imaging (DTI) to parcellate the human cingulate cortex (CC) based on resting‐state functional connectivity (rsFC) patterns and anatomical connectivity (AC) patterns, to analyze the rsFC patterns and the AC patterns of different subregions, and to recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…Furthermore, in our study, the ROIs were selected based on the AAL template (Tzourio-Mazoyer et al, 2002 ; Rolls et al, 2015 ), which parcellates the cingulate into fairly large anterior, mid, and posterior cingulate regions. A recent study proposed a cingulate parcellation scheme at the subregional level, which showed consistency of functional connectivity with anatomical subregions (Jin et al, 2018 ). Future stimulation-related studies may focus on small cingulate subregions, thus enhancing our understanding of stimulation's impact on cingulate subregional levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our study, the ROIs were selected based on the AAL template (Tzourio-Mazoyer et al, 2002 ; Rolls et al, 2015 ), which parcellates the cingulate into fairly large anterior, mid, and posterior cingulate regions. A recent study proposed a cingulate parcellation scheme at the subregional level, which showed consistency of functional connectivity with anatomical subregions (Jin et al, 2018 ). Future stimulation-related studies may focus on small cingulate subregions, thus enhancing our understanding of stimulation's impact on cingulate subregional levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Beckmann et al 2009 ; Yu et al 2011 ; Jin et al 2018 ) have examined the connectivity of the human cingulate regions with structural methods, in which diffusion-weighted MR images are used to track white-matter pathways, and/or resting state functional MRI, in which correlations in spontaneous activity at rest between brain regions are assumed to reflect connectivity. One recent study (Oane et al 2020 ) has even used intracranial stimulation to track cingulate connections.…”
Section: Connectivity Of Human and Macaque Csv (Mri)mentioning
confidence: 99%
“…The connectivity of this cluster was predominantly with parietal, motor and premotor cortex. Jin et al ( 2018 ) used both connectivity methods and described six clusters based on functional connectivity and ten based on structural connectivity. One of their structural clusters (S7) had a similar location to CSv.…”
Section: Connectivity Of Human and Macaque Csv (Mri)mentioning
confidence: 99%
“…A number of functional and anatomical parcellation studies suggest that subdivisions of the ACC and their patterns of connectivity may provide regional specialization to support this diverse array of functions (Balsters et al, 2016; Beckmann et al, 2009; Fan et al, 2016; Glasser et al, 2016; Jin et al, 2018; Neubert et al, 2015; Torta et al, 2013; Yu et al, 2011). Co-activation of dorsal versus rostral ACC and particular limbic structures may relate to their respective roles in the appraisal of emotion (e.g., dorsal ACC and anterior insula connectivity) versus more regulatory demands (e.g., rostral/ventral ACC and amygdala connectivity) (Dosenbach et al, 2006; Egner et al, 2007; Etkin et al, 2006, 2011; Giuliani et al, 2011; Seeley et al, 2007).…”
Section: Discussionmentioning
confidence: 99%